MENGATASI KEKERASAN BERBASIS GENDER DI ERA DIGITAL: PERAN PEMERINTAH DAN TEKNOLOGI DALAM UPAYA PERLINDUNGAN PEREMPUAN - Rahma Yanti, Asni; Nasution, Muhammad Irwan Padli (Jurnal Res Justitia: Jurnal Ilmu Hukum, 2025)
Women’s safety in public and digital spaces has become a major concern in recent decades due to the rise in genderbased violence. In addressing these challenges, collaboration between government and technology plays a critical role in preventing, detecting, and responding to threats. This study aims to explore the synergy between government policies and technological innovations to improve women’s safety and surveillance in both spaces. Using a qualitative approach, this study analyzes various government policies, AI-based surveillance technologies, security applications, and big data collection in creating safe spaces for women. The results show that while technology offers significant solutions, challenges such as data privacy and gaps in access to technology require special attention in the implementation of these policies. Collaboration between government and the private sector needs to be strengthened to ensure the sustainability and effectiveness of technology-based security programs